Changing midlife tropes: A transcendence into epiphany - Niehaus, Louisa (The Indo-Pacific journal of phenomenology, 2025)
Midlife is often stereotyped as a time of turbulence, angst and chaos, marked by inappropriate behaviours, broken marriages, infidelity and destructive changes. However, this article aims to challenge these stereotypes and present a different perspective. It argues that midlife is not a crisis; instead, it is a transformative journey into epiphany. This transcendent midlife journey is possible through gaining self-awareness, garnering insights and resonating with accumulated inherent (and previously undiscovered) values and desires. This starkly counters dated and prescriptive narratives that, left unchecked, descend into negative midlife tropes. Navigating this necessary period in adult actualisation has the potential to be deeply transformative and equip the adult at midlife to live a more meaningful and aligned life. This article presents a detailed discussion and findings from the journeys of five research participants who transitioned from midlife crisis to epiphany. Each participant’s life story is analysed, drawing on themes from existing literature on midlife crises and emphasising the variables of transcendence and evolution into epiphany. The article challenges conventional tropes and describes the unique epiphanies that resulted from these transcendent journeys, providing a rich and diverse perspective on midlife transitions.